Decrease of Murine Cytomegalovirus–Induced Retinitis by Intravenous Delivery of Immediate Early Protein-3–Specific siRNA - Marshall, Brendan (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. Retinitis induced by both human and murine cytomegaloviruses following immunosuppression is characterized by progressive loss of retinal architecture, due to necrosis of virus-infected cells as well as widespread apoptosis of uninfected bystander cells. Because small inhibitory RNA molecules (siRNA) can reduce murine cytomegalovirus (MCMV) gene expression and thereby inhibit virus replication in vitro, we tested siRNAs directed against MCMV immediate early protein-3 (IE-3) to determine if MCMV-induced retinitis could be alleviated in vivo. METHODS. Immunosuppressed Balb/c mice (2.0 mg methylprednisolone acetate every 3 days beginning on day −2) were infected with 5 × 10(3) pfu of the K181 strain of MCMV via the supraciliary route. At day 2 post infection, mice were treated with various doses of IE-3–specific siRNA ranging from 0.1 nmol to 10 nmol, in a volume of 20 μL PBS via tail vein injection. Injected eyes were collected at various times post inoculation and subjected to plaque assay for virus titer, MCMV antigen staining, H&E staining, TUNEL assay, and Western blot for MCMV IE-3 protein. RESULTS. Small but significant amounts of fluorescently labeled IE-3–specific siRNA localized to the RPE layer 48 hours after intravenous injection. IE-3–specific siRNA significantly reduced virus titers at all concentrations tested (ranging from 0.1 nmol to 10 nmol), but the most potent effect of siRNA was observed at a dose of 1 nmol. We also observed that IE-3–specific siRNA produced a substantial decrease in MCMV titers and a substantial reduction in bystander cell apoptosis over the time course of virus infection. CONCLUSIONS. Systemic administration of IE-3–specific siRNA could alleviate MCMV retinitis by inhibiting virus replication and subsequent death of uninfected retinal cells.